KRITERIA DIAGNOSIS DAN PENATALAKSANAAN OTITIS MEDIA SUPURATIF KRONIS - Fairuziah Bader Alkatiri (DiscoverSys Inc., 2016)
Introduction: Otitis media is an inflammation of part or all of the mucosa of the middle ear, Eustachian tube, mastoid antrum, and mastoid cells. Patients with middle ear disease often comes as a chronic stage that causes hearing loss and expense secretions. Patients complain of hearing loss that disrupt the function of the social, educational and professional. School-age children may show poor results at school. One type of otitis media is chronic suppurative otitis media (CSOM), which is a chronic infection of the middle ear with tympanic membrane perforation and discharge of secretions from the middle ear continuous or intermittent, usually accompanied by hearing loss. Secretions may be thin or thick, clear or in the form of pus. CSOM formerly called otitis media with perforated. Diagnosis is made by history, physical examination. Two types of classification that is often used is CSOM types of benign and malignant types, and based on the activity of secretions out. Management of sudden deafness include conservative with some medical therapy depends on the type of CSOM and accompanying complications.Case: Male patient, 47 years old, came with complaints of discharge from the left ear since 1 month ago. Discharge yellowish-white, slightly viscous, odorless, out a little, and not itchy. Patients with a history of diabetes. Patients admitted before the water could get into the ear while swimming in the sea. At the present status and status generalist within normal limits. On the left ear found mucopurulent secretions. On the left tympanic membrane perforation in the visible region of the central part postero superior.Â